Carbon capture and liquefaction from methane steam reforming unit: 4E's analysis (Energy, Exergy, Economic, and Environmental). (15th February 2023) - Choe, Changgwon; Haider, Junaid; Lim, Hankwon
Graphical abstract: Highlights: Comprehensive assessment in terms of 4E's analysis of CO2 liquefaction is performed. CO2 liquefaction is evaluated in technical, economic, and environmental aspects. Techno-economic and life-cycle assessments are performed for liquefaction processes. Multi-criteria decision analysis is conducted based on the 4E's assessment results. Abstract: Excessive fossil–fuel consumption to meet increased energy demand is considered as the main reason of the climatic change. To prevent this devastating change, hydrogen has gained much attention as an intermediate to replace fossil–fuel–based energy systems by sustainable green energy system. Since most of the H2 is produced through natural gas process, a trade–off in terms of huge amounts of CO2 emissions should be concerned. Accordingly, integration of the H2 production and carbon capture facility actively, called blue H2, emerges as a workable alternative. In addition, with the rise in CO2 demand, the liquefaction of captured CO2 has become an attractive strategy in terms of long–term storage and transportation. Therefore, a comprehensive study is performed to assess the feasibility of an integrated system based on carbon capture using monoethanol amine and four CO2 liquefaction systems such as Linde-Hampson, dual pressure Linde-Hampson, vapor compression refrigerant, and absorption refrigerant systems (later will use as case 1 to 4, respectively). Based on energy and exergy evaluations, case 4 reflects the higher efficiencies with specific energy consumption of 0.188el and 0.733th GJ ton CO2 -1 and exergy efficiency of 85.55 %. In addition, techno-economic analysis calculates unit LCO2 production of each case; 22.19, 21.35, 21.00, and 24.60 ton -1 for cases 1, 2, 3, and 4, respectively. The quantified climate change impacts were estimated by life-cycle assessment; 0.629, 0.620, 0.608. and 0.674 kg CO2 -eq kg LCO2 -1 for cases 1, 2, 3, and 4, respectively. Furthermore, analytic hierarchy process is performed to provide comprehensive guidelines of liquefied CO2 production under technical, economic, and environmental aspects.